From parachuting to partnership: Fostering collaborative research in protected areas - Smit, I. P. J. (2024)
1. Research in protected areas (PAs) is often dominated by scientists from outside the conservation agencies managing them. This can potentially lead to misalignment with local needs, insensitivity to the local context and a lack of investment in and use of local expertise. These issues often arise when international researchers work in another country without local engagement (known as ‘parachute science’). Despite PAs being key end users of actionable science, there is limitedunderstanding of the prevalence and impact of parachute science in these areas.2. Here, we investigate parachute versus collaborative research in two national parks in the Global South (Kruger National Park, South Africa; Nahuel Huapi National Park, Argentina) and one park from a developed economy (Kakadu National Park, Australia). To explore the prevalence, risks, benefits and complexities of research practices, we analyse the patterns of authorship, funding and acknowledgement in a random sample of peer-reviewed papers from research conducted in these parks.3. Our findings show a higher incidence of potential parachute science in Kruger National Park (18% of papers with only out-of-country authors) compared to Nahuel Huapi (4%) and Kakadu (2%) national parks. However, the occurrence of internationally collaborative research (national and international authors) was double in Global South parks (35%–38%) than in the Australian park (18%).4. The study illustrates the potential benefits of international collaboration for PAs, including increased research productivity, expanded funding sources and possibly higher impact and visibility of published studies. PAs in developed countries may have fewer opportunities to obtain those benefits.5. Most papers, even those with in-country authors, lacked authors affiliated with the agency managing the PA and often failed to even acknowledge these agencies. This suggests the potential for a different form of parachute science (which we term ‘park parachuting’) in which lack of local involvement may hamper integration of research with management. 6. Synthesis and applications: Establishing conditions that foster collaboration between national and international researchers, and between PA agency staff and external researchers (regardless of their nationality), would enable parks to better serve as catalysts for research collaboration. This collaborative approach can facilitate access to additional funding, enhance research capacity, increase research productivity and amplify research impact.